Kargoisme dan Messianik Politik Etik Ero-Amerika - Ibrahim Peyon (CENDERAWASIH: Jurnal Antropologi Papua, 2021)
Cargoism is a belief in prosperity, happiness and eternal life brought by certain figures. Cargoism was constructed by western anthropologists and missionaries who had lived and worked in Melanesia. The western anthropologists and missionaries observed various social and cultural movements in Melanesia, which could then be conceptualized and theorized in social theory under the name of the Cargoism Movement. This view of Corgoism does not exist in Melanesian culture, but it is a western view related with their mobilization of cargo economic and materially in western society. Cargoism and messianic were shaped by Western anthropologists and European missionaries for the benefit of their colonialism and Christianization. In Melanesia there is no cargoism and messianic as Western anthropologists and missionaries write. Social and political movements labeled as cargoism or messianic are nationalist movements to expel colonialism and fight for the sovereignty of the Melanesian peoples